2022
DOI: 10.1155/2022/7548145
|View full text |Cite
|
Sign up to set email alerts
|

Specific PFKFB3 Inhibitor Memorably Ameliorates Intervertebral Disc Degeneration via Inhibiting NF-κB and MAPK Signaling Pathway and Reprogramming of Energy Metabolism of Nucleus Pulposus Cells

Abstract: Intervertebral disc (IVD) degeneration (IVDD) is a characteristic of the dominating pathological processes of nucleus pulposus (NP) cell senescence, abnormal synthesis and irregular distribution of extracellular matrix (ECM), and tumor necrosis factor-α (TNF-α) induced inflammation. Nowadays, IVD acid environment variation which accelerates the pathological processes mentioned above arouses researchers’ attention. KAN0438757 (KAN) is an effective inhibitor of selective metabolic kinase phosphofructokinase-2/fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The NF‐κB pathway, which is intricately associated with inflammation and apoptosis, has been demonstrated to play a crucial role in IVDD 30 . In a recent investigation by Cao et al., 55 it was reported that inhibition of the NF‐κB pathway led to reprogramming of the energy metabolism in NPCs. Furthermore, Zheng et al 56 .…”
Section: Discussionmentioning
confidence: 99%
“…The NF‐κB pathway, which is intricately associated with inflammation and apoptosis, has been demonstrated to play a crucial role in IVDD 30 . In a recent investigation by Cao et al., 55 it was reported that inhibition of the NF‐κB pathway led to reprogramming of the energy metabolism in NPCs. Furthermore, Zheng et al 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, Piezo1 exerts an anti-inflammatory effect by inhibiting the NF-κB pathway, without impacting the extracellular signal-regulated kinase (ERK) and p38 pathways. 15 This anti-inflammatory influence is demonstrated through the inhibition of LPS-induced microglial activation and the production of pro-inflammatory factors TNF-α and IL-6. However, conflicting results have been reported regarding the impact of Piezo1 activation on pro-inflammatory cytokine release, with studies indicating both inhibitory and stimulatory effects depending on the experimental conditions, including the concentration of the Piezo1 activator Yoda.…”
Section: Piezo Channels In Alzheimer's Disease: Connecting the Dotsmentioning
confidence: 99%